2010
DOI: 10.1080/1360080x.2011.537013
|View full text |Cite
|
Sign up to set email alerts
|

Perceived discrimination and international students' learning: an empirical investigation

Abstract: At a time when the number of internationally mobile students worldwide has been growing steadily, the US share of this market has been declining. Since, as it is often claimed, international students are the best ambassadors for their host countries, an effective recruitment strategy is to enhance their learning experience, with the expectation that others will hear about it. In a post 9/11 environment, we focus on the importance of non-discriminatory environments to bring about successful learning outcomes, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…Engagement manifests in students' involvement in their work, enhanced commitment in spite of obstacles and challenges and concerted and visible efforts in achieving learning outcomes (Fletcher 2005 ;Kenny et al 1995 ;Kuh et al 2008 ;Newmann 1992 ;Taylor and Parson 2011 ;Vandewalle et al 1995 ;Willms 2003 ). Strong evidence is found in literature that quality education significantly affects students' engagement (Karuppan and Barari 2011 ;Kuh et al 2008 ;Stukalina 2011 ;Yam et al 2013 ).…”
Section: Students' Engagementmentioning
confidence: 99%
“…Engagement manifests in students' involvement in their work, enhanced commitment in spite of obstacles and challenges and concerted and visible efforts in achieving learning outcomes (Fletcher 2005 ;Kenny et al 1995 ;Kuh et al 2008 ;Newmann 1992 ;Taylor and Parson 2011 ;Vandewalle et al 1995 ;Willms 2003 ). Strong evidence is found in literature that quality education significantly affects students' engagement (Karuppan and Barari 2011 ;Kuh et al 2008 ;Stukalina 2011 ;Yam et al 2013 ).…”
Section: Students' Engagementmentioning
confidence: 99%
“…For example, increased discrimination has been associated with higher rates of depression among Asian students, above and beyond general everyday stress (Wei, Ku, Russell, Mallinckrodt, & Liao, 2008). Additionally, studies have shown that perceived discrimination lowers students' satisfaction with attending a U.S. university (Wadsworth, Hecht, & Jung, 2008) and can negatively impact students' educational experience (Karuppan & Barari, 2011).…”
Section: Correlates Of Depressive Symptoms Among International Studentsmentioning
confidence: 99%
“…This difference in academic training poses immense challenges which, when not overcome, may result in other non-academic issues. Inability to overcome the language barrier does not only lead to poor academic performance (FassHolmes & Vaughn, 2014) but also leads to diminished self-reliance (Hung & Hyun, 2010), and increased perception of discrimination (Karuppan & Barari, 2011). More serious psychiatric issues have been linked to academic difficulties and poor language skills among East Asian students (Mitchell, Greenwood & Guglielmi, 2007).…”
Section: Linguistic Quadrantmentioning
confidence: 99%